Utility of Surgical APGAR Score in Risk Stratification for Emergency Gastrointestinal Procedures: A Prospective Analysis - Naresh, P.; Kumar, Thogari Kranthi; Dasari, Lalith (Journal of Neonatal Surgery, 2025)
Background: Emergency gastrointestinal surgery is associated with significant morbidity and mortality. The Surgical APGAR Score (SAS), a simple 10-point scoring system based on intraoperative parameters, has shown promise in predicting postoperative complications. This study aimed to evaluate the utility of SAS in predicting outcomes following emergency gastrointestinal procedures. Methods: A prospective cross-sectional study was conducted on 30 patients undergoing emergency gastrointestinal surgery under general anesthesia at Mamata Medical College, Khammam, from October 2019 to September 2021. SAS was calculated using lowest heart rate, lowest mean arterial pressure, and estimated blood loss. Patients were followed for 30 days to assess major complications and mortality. Statistical analysis included correlation between SAS scores, complications, and ASA grades. Results: The mean age was 45.46 ± 16.05 years with slight female predominance (53.3%). Acute intestinal perforation was the most common diagnosis (30%). SAS distribution showed 40% high-risk (0-4), 53.3% medium-risk (5-7), and 6.7% low-risk (8-10) patients. Patients with complications had significantly lower mean SAS scores compared to those without complications (4.65 ± 1.78 vs 6.20 ± 1.22, p=0.001). A strong inverse correlation existed between ASA grade and SAS score (F=44.76, p<0.0001). The 30-day mortality rate was 6.7%. Major complications included prolonged ventilation (13.3%) and wound dehiscence (13.3%). Conclusions: The Surgical APGAR Score effectively predicts postoperative complications in emergency gastrointestinal surgery. Its simplicity and immediate availability make it a valuable tool for risk stratification and clinical decision-making. Implementation of SAS can enhance patient safety and optimize resource allocation in emergency surgical settings